DYNAMICS OF COPYRIGHT PROTECTION IN THE ERA OF GLOBALIZATION: A COMPARATIVE STUDY OF INTERNATIONAL LAW - Dinda Prama Suari; Rina Arum Prastyanti Prastyanti (Universitas Budi Luhur, 2025)
Abstract: In this era of globalization and advances in digital technology, the copyright protection system faces increasingly complex challenges. This research is a normative law study with a comparative approach to legal systems in developed and developing countries, as well as the role of global institutions in shaping international norms. The study examines key legal instruments such as the Bern Convention, TRIPS Agreement, and WIPO Copyright Treaty (WCT), and evaluates their implementation in various countries. The results show that developing countries like Indonesia still face obstacles in the implementation of copyright protection, ranging from weak digital law enforcement to low public awareness. The study emphasizes the need for inclusive global governance so that the copyright protection system can be fairly adapted to domestic conditions. Abstrak: Dalam era globalisasi dan kemajuan teknologi digital ini, sistem perlindungan hak cipta menghadapi tantangan yang semakin kompleks. Penelitian ini adalah studi hukum normatif dengan pendekatan komparatif terhadap sistem hukum di negara maju dan berkembang, serta peran lembaga global dalam membentuk norma internasional. Studi ini meneliti instrumen hukum utama seperti Konvensi Bern, Perjanjian TRIPS, dan Perjanjian Hak Cipta WIPO (WCT), serta mengevaluasi penerapannya di berbagai negara. Hasil penelitian menunjukkan bahwa negara-negara berkembang seperti Indonesia masih menghadapi hambatan dalam pelaksanaan perlindungan hak cipta, mulai dari penegakan hukum digital yang lemah hingga rendahnya kesadaran publik. Studi ini menekankan perlunya tata kelola global yang inklusif agar sistem perlindungan hak cipta dapat disesuaikan secara adil dengan kondisi domestik.